The Use of Fengshui in Keraton Kasepuhan Cirebon - Nita Auliasari; C. Dewi Hartati (Bambuti, 2020)
This article shows the application of fengshui in Keraton Kasepuhan. The application of fengshui also shows the acculturation of Chinese culture in Kertaon Kasepuhan. This study uses a qualitative research method which data collection uses literature study, interviews, observation, and documentation. The results showed that Keraton Kasepuhan applied fengshui at the location of the palace, namely its position facing the sea with its back to the mountain. The shape of the building has the advantageous shape of a rectangle. The fengshui elements used in Keraton Kasepuhan building are in the form of color, room lighting, the symbol of plants and animals, and fengshui decorative symbols. The application of fengshui at Keraton Kasepuhan is carried out in order to get the benefits of balance or harmony.